A Unique Case of Bilateral Synchronous Testicular Tumor with Concomitant Bilateral Diffuse Intratubular Germ Cell Neoplasia: Testis Sparing Surgery and Local Radiotherapy - Yuksel, Mehmet B. (S. Karger AG, 2013)
Synchronous bilateral testicular germ cell tumors (TGCTs) are seen in exteremely rare cases. Although there is still no standard therapy for bilateral TGCTs, bilateral orchiectomy is recommended as the gold standard treatment. Nevertheless, it has some long-term problems, such as infertility and psychosocial difficulties, and thus some clinicians prefer to perform testis-sparing surgery in appropriate cases. We reviewed the first case of bilateral synchronous TGCT with concomittant bilateral diffuse intratubular germ cell neoplasia in a young single patient, who was treated by a left radical orchiectomy and right testis sparing-surgery with following local radiotherapy to the right residual testicular tissue with previous semen cryopreservation to maintain the ability to father children. We supposed that testis-sparing surgery can be a feasible therapeutic alternative to radical orchiectomy in patients with bilateral TGCTs in terms of improving the quality of life and continuing fertility and normal hormonal status with no medications. However, while the long-term effects are not yet known, this type of treatment should be perpormed in carefully selected cases with longlife expectancy.